Sistem Pengelolaan Air Limbah Industri Pangan Sebagai Pemanfaatan Air ke Tanah: Systematic Literature Review - Dewi Purnamawati; Crys Sena Puspitasari (Jurnal Persada Husada Indonesia, 2026)
Background: The surge in global population drives the intensification of the food industry, resulting in high freshwater consumption and elevating the risks of water scarcity. Conversely, poorly managed food industrial wastewater disposal threatens the quality of surface and groundwater. This study aims to evaluate and synthesize scientific evidence regarding the effectiveness of various food industry wastewater treatment technologies to support sustainable land application. Methodology: This study applied the Systematic Literature Review (SLR) method following the PRISMA guidelines. Article searches were conducted via Google Scholar, ScienceDirect, and Pubmed databases for publications spanning 2016–2024. Results: Out of 280 identified articles, 12 met the inclusion criteria for synthesis. The literature analysis identified three main pillars: technology diversification (such as anaerobic systems for tofu waste, MBR membrane filtration, and zeolite anocomposites), water circularity efficiency through the Zero Liquid Discharge (ZLD) concept that massively conserves water, and the conversion of byproducts into organic fertilizers (liquid and compost). Treated effluent proved safe and rich in natural nutrients for alternative irrigation without the risk of hazardous heavy metal accumulation in soil and crops. Conclusion: Integrated and automated food industrial wastewater management provides a double impact: preventing aquatic environmental degradation while supporting agricultural sustainability through resource circularity